HUBUNGAN RIWAYAT ANEMIA PADA KEHAMILAN IBU DENGAN HIPERBILIRUBINEMIA PADA BAYI BARU LAHIR: Literature Review - Elsa Fitri Jaymar Salpan (2020)
THE RELATIONS OF ANEMIA HISTORY ON MATERNAL PREGNANCY WITH HYPERBILIRUBINEMIAOF A NEWBORN: A LITERATURE REVIEW Hyperbilirubinemia in newborns is a condition when the baby's skin, conjunctiva, and mucosa turn yellow or jaundice. This condition is caused by an increase in bilirubin levels in infants. Hyperbilirubinemia is a common and natural occurrence in newborns, but if not treated quickly and appropriately will cause kernicterus in infants, even death. This literature review aims to explain the relations of anemia history on maternal pregnancy with hyperbilirubinemia of a newborn. This literature review was compiled by searching for articles related to anemia in pregnant women and hyperbilirubinemia in newborns. These articles were obtained from various international and national electronic databases, such as Google Scholar, Science Direct, and Portal Garuda. Only 14 articles were used or fulfilled the inclusion criteria. Keywords to search for articles used are "hyperbilirubinemia", "anemia", "newborn babies", and "pregnant women". Inclusion criteria which taken for the references are articles that published from 2015-2020, articles that can be downloaded in full text, and research that has been indexed Sinta and Scopus. This literature review prove that the relations of anemia history on maternal pregnancy with hyperbilirubinemia of a newborn. This tends to be due to Low Birth Weight (LBW) conditions that occur in newborns. LBW can be caused by anemia experienced by the mother during pregnancy. Anemia in pregnant women was caused by nutrition consumed that mothers took during pregnancy and mothers not routinely consume Fe tablets.This study provides valid evidence by looking for journals that have been indexed nationally and internationally, aboutthe relations of anemia history on maternal pregnancy with hyperbilirubinemia of a newborn. Keyword: Hyperbilirubinemia, anemia, newborns, pregnant women.